(untitled) (Research, Society and Development, 2022)
The professional nurse, responsible for performing nursing care in environments in which health care is offered, with its own laws and regulations. Nursing has three categories, and the nurse is a professional with a higher education course, thus, teaching in nursing schools should include from the teaching of basic content to critical care in nursing. To make teaching assertive, the use of technology is necessary, such as the use of controlled simulation resources, which provides the student with practical experience without harm to the patient and with fewer gaps in teaching. Methodology: This is an integrative literature review study, using pre-defined criteria for choosing and selecting articles. Results: After using the pre-established criteria, a total of 23 articles were found. Thus, after reading, subdivisions were chosen for better discussion regarding the theme of teaching in critical care. Thus, the discussion was contextualized in subthemes: relationship of critical thinking and decision making during graduation; use of a virtual environment for teaching; use of a face-to-face controlled environment in critical care teaching. Conclusion: The teaching of critical skills nowadays is facilitated by technological resources, which allow the undergraduate to develop technical and emotional skills and competencies and to improve interprofessional relationships, with the aim of reducing damage and negative experiences to the student and also to the final client of this training, the patient.